Crossing Histories and Ethnographies: Following Colonial Historicities in Timor-Leste - Roque, Ricardo (2019)
The key question for many anthropologists and historians today is not whether to cross the boundary between their disciplines, but whether the idea of a disciplinary boundary should be sustained. Reinterpreting the dynamic interplay between archive and field, these essays propose a method for mutually productive crossings between historical and ethnographic research. It engages critically with the colonial pasts of indigenous societies and examines how fieldwork and archival studies together lead to fruitful insights into the making of different colonial historicities. Timor-Leste’s unusually long and in some ways unique colonial history is explored as a compelling case for these crossings.